Temporal characteristics of facial ensemble in individuals with autism spectrum disorder: examination from arousal and attentional allocation - Harada, Yuki; Ohyama, Junji; Sano, Misako; Ishii, Naomi; Maida, Keiko; Wada, Megumi; Wada, Makoto (Frontiers in Psychiatry, 2024)
Introduction Individuals with Autism Spectrum Disorder (ASD) show atypical recognition of facial emotions, which has been suggested to stem from arousal and attention allocation. Recent studies have focused on the ability to perceive an average expression from multiple spatially different expressions. This study investigated the effect of autistic traits on temporal ensemble, that is, the perception of the average expression from multiple changing expressions. Methods We conducted a simplified temporal-ensemble task and analyzed behavioral responses, pupil size, and viewing times for eyes of a face. Participants with and without diagnosis of ASD viewed serial presentations of facial expressions that randomly switched between emotional and neutral. The temporal ratio of the emotional expressions was manipulated. The participants estimated the intensity of the facial emotions for the overall presentation. Results We obtained three major results: (a) many participants with ASD were less susceptible to the ratio of anger expression for temporal ensembles, (b) they produced significantly greater pupil size for angry expressions (within-participants comparison) and smaller pupil size for sad expressions (between-groups comparison), and (c) pupil size and viewing time to eyes were not correlated with the temporal ensemble. Discussion These results suggest atypical temporal integration of anger expression and arousal characteristics in individuals with ASD; however, the atypical integration is not fully explained by arousal or attentional allocation.